1980
DOI: 10.3171/jns.1980.53.4.0541
|View full text |Cite
|
Sign up to set email alerts
|

Hyperextension injury of the cervical spine with esophageal perforation

Abstract: A case is presented of esophageal perforation following a hyperextension-flexion cervical injury. The patient recovered without complication. Hyperextension-flexion injuries of the cervical spine have proved to be a rare cause of esophageal perforation. The mechanism may be impingement of the esophagus against an exostosis or the edge of a vertebral body, or entrapment of the esophageal wall between the vertebral bodies as hyperextension changes to flexion. If not detected and treated early, the perforation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Prior to that several articles have commented on the incidence of esophageal or pharyngeal injury as related to cervical spine fractures themselves or the mechanism that caused the original injury. It is often easy to forget that a patient with a severe cervical injury may already have a tear, stretch or other soft tissue injuries to the structures of the neck and that subsequent trauma of surgery aggravates the situation, or the injury is originally missed in an intubated patient [7,8,4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to that several articles have commented on the incidence of esophageal or pharyngeal injury as related to cervical spine fractures themselves or the mechanism that caused the original injury. It is often easy to forget that a patient with a severe cervical injury may already have a tear, stretch or other soft tissue injuries to the structures of the neck and that subsequent trauma of surgery aggravates the situation, or the injury is originally missed in an intubated patient [7,8,4].…”
Section: Resultsmentioning
confidence: 99%
“…incidence of pharyngeal or esophageal injuries has been reported to be 0.1% after anterior cervical spine surgery [6]. While esophageal injuries may not be extremely rare, the development of an esophageal injury into an esophagocutaneous fistula has been reported fewer than ten times [2,3,8,9]. Pharyngocutaneous or esophagocutaneous fistulae are always associated with injuries to the esophagus.…”
mentioning
confidence: 99%
“…The inci dence of these problems is unknown; however, a search of the literature with the Medical Literature Analysis and Retrieval System (MEDLARS) database from 1900 to the present time revealed 32 patients with cervical fractures from blunt trauma who also had an oesophageal perforation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] This investigation of the literature also revealed that oesophageal injuries are more common with penetrating neck injuries than from blunt trauma.…”
Section: Introductionmentioning
confidence: 99%
“…17,27,45 One of these spaces, the retropharyngeal space (RPS), may be secondarily contaminated and may lead to the formation of an abscess and osteomyelitis. Because of the proximity of the oropharynx (a naturally contaminated region) to the spinal structures of the craniocervical junction, it is possible that small mucosal lacerations in the oropharynx caused by unstable traumatic craniocervical injuries may become contaminated and lead to secondary infection and osteomyelitis.…”
mentioning
confidence: 99%
“…17,27,45 One of these spaces, the retropharyngeal space (RPS), may be secondarily contaminated and may lead to the formation of an abscess and osteomyelitis.…”
mentioning
confidence: 99%